Paradise from behind the Iron Curtain Reading, translating and staging Milton in Communist Hungary - Péti, Miklós (Literature and Translation, 2022)
Paradise from behind the Iron Curtain provides a detailed survey of the key responses to Milton's work in Hungarian state socialism. The four decades between 1948 and 1989 saw a radical revision of previous critical and artistic positions and resulted in the emergence of some characteristically Eastern European responses to Milton's works. Critical and artistic appraisals of Milton's works in the communist era proved more controversial than receptions of other major Western authors: on the one hand, Milton's participation in the Civil War earned him the title of a 'revolutionary hero,' on the other hand, religious aspects of his works were often disregarded and sometimes proactively suppressed. Ranging through all the genres of Milton's oeuvre as well as the critical tradition, the book highlights these diverging responses and places them in the wider context of socialist cultural policy. In addition, the author presents the full Hungarian script of the 1970 theatrical performance of Milton's Paradise Lost, the first of its kind since the work's publication, including a parallel English translation, which enables a deeper reflection on Milton's original theodicy and its possible interpretations in communist Hungary.